1985
DOI: 10.1136/oem.42.8.517
|View full text |Cite
|
Sign up to set email alerts
|

Occupational asthma in a steel coating plant.

Abstract: An outbreak of occupational asthma, of unknown cause and extent, was detected in a steel coating plant. In 1979 a cross-sectional study which defined occupational asthma in terms of respiratory symptoms detected 21 people with suggestive symptoms among the 221 studied. They all worked in the coating shop, but the plastic coatings used at the plant contained many potential sensitising agents that might have caused the asthma. All 21 developed their symptoms after 1971, and it was found that in this year a suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…This is because they are far too weakly associated with the development of workrelated asthma, symptoms or other signs of work-related asthma (*) [143][144][145]. 9) Early detection of work-related respiratory symptoms, sensitisation and work-related asthma is possible using medical surveillance, which includes a questionnaire in combination with at least one of the following options: detection of specific sensitisation, NSBHR testing, SIC, diagnostic work up in a referral centre (**) [57,123,[147][148][149][150][151][152][153].…”
Section: Strong Lowmentioning
confidence: 99%
“…This is because they are far too weakly associated with the development of workrelated asthma, symptoms or other signs of work-related asthma (*) [143][144][145]. 9) Early detection of work-related respiratory symptoms, sensitisation and work-related asthma is possible using medical surveillance, which includes a questionnaire in combination with at least one of the following options: detection of specific sensitisation, NSBHR testing, SIC, diagnostic work up in a referral centre (**) [57,123,[147][148][149][150][151][152][153].…”
Section: Strong Lowmentioning
confidence: 99%
“…(64) A 10 percent OA prevalence rate was reported as well among employees assigned to a process in which steel was coated with a plastic nish that was later found to have included a TDIbased component (21 cases determined mostly based on questionnaire responses among 221 employees). (56) The coated steel was oven-cured, apparently releasing fumes containing TDI at concentrations (HPLC analysis) of up to 26 ppb. After excluding the TDI-based component in 1979, no new OA cases were identi ed in a subsequent survey about nine months later.…”
Section: Health Outcomes In Tdi-using Industriesmentioning
confidence: 99%
“…During the past 15 years, measures of prevalences between zero and 10 percent have been observed (27) 1978 66 Foam production Clinical evidence Survivor population 3.0 White et al, (28) 1980 147 Sewing laminated MD opinion Frequent pre-existing 0.7 nylon respiratory symptoms Kido, (29) 1983 87 Lacquer varnishing Self-reported symptoms 16.0 Belin et al, (30) 1983 48 Foam production Clinical evidence Survivor population 0 Venables et al, (31) 1985 221 Foam coating of steel Mostly self-reported 9.5 symptoms Wang et al, (2) 1988 38 Adhesive tape Self-reported symptoms Small subgroups with 0 production mean exposures of 12, 38 21, and 47 ppb TDI 85 Huang et al, (13) …”
Section: Prevalence Of Tdi-asthma and Trendsmentioning
confidence: 96%